How Patients' Stories Shape Their Votes: The Role of Health Care in the 2018 U.S. Midterm Elections. (July 2019) - Gordon, Paul; Shapiro, Eve
Abstract : Reflecting on the 2018 U.S. midterm elections, it is clear that health care coverage once again played an important role. This prompted the authors to look back on their 2016 bike listening tour across the country when they asked people about their views on the Affordable Care Act. Through those conversations, the authors observed that a common thread was the rampant misunderstanding of health insurance coverage and the central role that politicians had in the creation of policy. In this Invited Commentary, the authors explore the results of the 2018 election, particularly in the rural northern areas where they toured in 2016, and the contradictions between what people say they want, what the candidates say they support, and what the facts actually show. They offer suggestions for the role physicians might play with patients in correcting misunderstandings about the health care system and the policies that shape it. Patients do not always make decisions as physicians do. As opposed to evidence and data, they might rely on personal experiences and stories. The authors suggest that physicians might be able to help patients use these stories to inform their decisions, and to help them understand the connection between their personal health care experiences and the votes they cast in elections.